2007
DOI: 10.2117/psysoc.2007.76
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Olfactory Store in Working Memory?

Abstract: We tested the hypothesis that olfactory information can be temporarily retained in a modality-specific short-term memory system. The results of two experiments using short-term memory tasks supported this hypothesis. Experiment 1 showed an effect of concurrent odour memory on digit recall that was equivalent to the effect of concurrent visual memory and smaller than that of concurrent verbal memory. Experiment 2 showed a detrimental effect of concurrent odour memory on odour recognition, and no effect of concu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 36 publications
4
29
0
Order By: Relevance
“…Indeed, previous work from our laboratory (Johnson & Miles, 2009;Johnson, Cauchi & Miles, 2013) has demonstrated that the serial position function for olfactory memory differs to that observed for the visual and auditory domains. These differences might suggest the existence of an olfactory-specific slave system within working memory (Andrade & Donaldson, 2007), and the present data perhaps point towards similar dissociation for gustatory memory. One might speculate that the different requirements for the processing of the chemical senses have necessitated a functionally different memory system to that of 'far senses' such as vision.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Indeed, previous work from our laboratory (Johnson & Miles, 2009;Johnson, Cauchi & Miles, 2013) has demonstrated that the serial position function for olfactory memory differs to that observed for the visual and auditory domains. These differences might suggest the existence of an olfactory-specific slave system within working memory (Andrade & Donaldson, 2007), and the present data perhaps point towards similar dissociation for gustatory memory. One might speculate that the different requirements for the processing of the chemical senses have necessitated a functionally different memory system to that of 'far senses' such as vision.…”
Section: Discussionsupporting
confidence: 66%
“…an olfactory-specific slave system, Andrade & Donaldson, 2007) or multidimensional (Baddeley, 2000). The multi-dimensional episodic-buffer (Baddeley, 2000) has the potential to operate as a store for stimuli currently neglected by the modular slave systems of the model.…”
Section: Introductionmentioning
confidence: 99%
“…These findings have been interpreted as evidence for the existence of an independent olfactory 'module' in working memory (e.g. see Andrade & Donaldson, 2007). This, in turn, allows the argument that evidence for Hebbian repetition learning for olfactory sequences does not merely reflect the learning of a particular verbal sequence.…”
Section: Introductionmentioning
confidence: 81%
“…Yet again, there is good evidence that there is a capacity for short-term memory in olfaction (e.g., White, 1998; Andrade and Donaldson, 2007). What is not clearly established is the representational code that underpins this, and whether it is instantiated discretely (i.e., a short-term olfactory module) or as a component of long-term memory (e.g., Yeshurun et al, 2008; Johnson and Miles, 2009).…”
Section: Differences Between Processing In Olfaction and Other Modalimentioning
confidence: 99%